Free Speech, Freedom of the Press, and the Tapestry of Lies - Mikael M. Karlsson (The University of Akureyri, 2015)
This paper comprises the text of the invited lecture presented at the international conference, "Tjáningarfrelsi og félagsleg ábyrgð - Kenningar og útfærsla" (Freedom of Expression and Social Responsibility – Theory and Practice), held at the University of Akureyri on 29 September 2014 and arranged by the Media Studies program and the Faculty of Social Sciences. Those who know his work will recognize here my debt to John Pilger, journalist and documentary film-maker, who has both informed and inspired me.